Sprachenwahl im Schweizer Frühfremdsprachenunterricht: (Folk-)linguistische Argumente in der öffentlichen Diskussion - Bleichenbacher, Lukas (My University, 2006)
In recent years, a number of German-speaking Swiss cantons have decided to introduce English, rather than the second national language, French, as a first foreign language in primary school. This paper offers an analysis of how the arguments in favour of the different options available to Swiss policymakers are represented in the public folklinguistic discourse of letters to editors to both German- and French-speaking newspapers. A majority of letter writers from the influential Zurich area clearly prefer English, whereas most French speakers favour the second national language. Crucially, only a minority of letter writers subscribe to the official policy, based on linguists’ recommendations, which plans to teach both foreign languages at an early stage. However, an in-depth discourse analysis of the letters to editors reveals that if the linguists manage to partake more actively in the public debate, the high aims of the new plurilingual policy may turn out not to be as far-fetched after all.
Keywords: language policy; multilingualism; folk linguistics; foreign language choice; Switzerland